Protocadherins, not prototypical: a complex tale of their interactions, expression, and functions - Weiner, Joshua A.; Jontes, James (Frontiers in Molecular Neuroscience, 2013)
The organization of functional neural circuits requires the precise and coordinated control of cell-cell interactions at nearly all stages of development, including neuronal differentiation, neuronal migration, axon outgrowth, dendrite arborization, and synapse formation and stabilization. This coordination is brought about by the concerted action of a large number of cell surface receptors, whose dynamic regulation enables neurons (and astrocytes) to adopt their proper roles within developing neural circuits. The protocadherins (Pcdhs) comprise a major family of cell surface receptors expressed in the developing vertebrate nervous system whose cellular and developmental roles are only beginning to be elucidated. In this review, we highlight selected recent results in several key areas of protocadherin biology and discuss their implications for our understanding of neural circuit formation and function.